Implementation of Financial Management to Improve Education Quality Based on the 2020 Education Unit Accreditation Instrument at MI Al-Ikhlas Karawang - Asri Khaerunnisa; Mulyawan Safwandy Nugraha (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to determine the implementation of financial management in improving the quality of education at MI Al-Ikhlas Karawang. This research focuses on how financial resources, especially BOS funds, are managed in accordance with the 2020 Education Unit Accreditation Instrument (IASP) standards. Descriptive qualitative research methods were used to provide an in- depth description of financial management practices at MI Al-Ikhlas Karawang. Data were collected through structured interviews with key stakeholders, including the principal, treasurer and teachers. These interviews provided insight into the financial decision-making process and resource allocation within the institution. The findings show that MI Al-Ikhlas Karawang relies solely on BOS funds as its main source of income. These funds are carefully allocated to support various educational activities, including the procurement of teaching materials, payment of staff salaries and maintenance of school facilities. The financial management practices observed ensure that the available resources are utilised efficiently to improve the quality of education provided. This study underlines the importance of strong financial management in achieving education quality. The effective utilisation of BOS funds has been instrumental in supporting school operational needs and educational initiatives. Recommendations include diversifying funding sources and improving financial planning to ensure long-term sustainability and continuous improvement of education outcomes